Making online learning accessible to disabled students: an institutional case study - Martyn Copper (Association for Learning Technology, 2006)
Based on the authors' reflections on experience working at the Open University, approaches to making online learning accessible to disabled students are considered. The considerations are applicable to all concerned with online learning and indeed anyone seeking to trade, disseminate information and mediate services online. In reflecting on the Open University experience of making online material accessible, pedagogic, organisational and cultural issues are highlighted and it is argued that it is important to address these issues in order to effect the organisational change needed to ensure that accessibility challenges are effectively met.